2009
DOI: 10.1093/nar/gkp002
|View full text |Cite
|
Sign up to set email alerts
|

Functional links between clustered microRNAs: suppression of cell-cycle inhibitors by microRNA clusters in gastric cancer

Abstract: microRNAs (miRNAs) play integral roles in diverse processes including tumorigenesis. miRNA gene loci are often found in close conjunction, and such clustered miRNA genes are transcribed from a common promoter to generate polycistronic primary transcript. The primary transcript (pri-miRNA) is then processed by two RNase III proteins to release the mature miRNAs. Although it has been speculated that the miRNAs in the same cluster may play related biological functions, this has not been experimentally addressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
354
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(376 citation statements)
references
References 32 publications
13
354
1
1
Order By: Relevance
“…As the qPCR analysis gave quantification of the mature miRNAs rather than their precursors, our analysis should have identified functional miRNAs that are important to gastric tumorigenesis. The involvement of Let-7, miR-21 and miR-221, and miR-222 and miR-148 in gastric carcinogenesis has been identified previously (Volinia et al, 2006;Motoyama et al, 2008;Zhang et al, 2008;Katada et al, 2009;Kim et al, 2009). These miRNAs, because they were annotated in our analysis, substantiate the validity of our approach.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As the qPCR analysis gave quantification of the mature miRNAs rather than their precursors, our analysis should have identified functional miRNAs that are important to gastric tumorigenesis. The involvement of Let-7, miR-21 and miR-221, and miR-222 and miR-148 in gastric carcinogenesis has been identified previously (Volinia et al, 2006;Motoyama et al, 2008;Zhang et al, 2008;Katada et al, 2009;Kim et al, 2009). These miRNAs, because they were annotated in our analysis, substantiate the validity of our approach.…”
Section: Discussionsupporting
confidence: 82%
“…In previous studies, miR-21 and let-7 have been shown to be oncogenic and suppressive with respect to GC, respectively (Motoyama et al, 2008;Zhang et al, 2008). A recent study also found overexpression of the miR-221 and miR-222 clusters in GC tissues and that these miRNAs target the Cip/Kip cell cycle regulators in GC cells (Kim et al, 2009). Transforming growth factor-b (TGFb) has pluripotent roles in regulating biological and pathological processes (van den Brink and Offerhaus, 2007;Massague, 2008).…”
Section: Introductionmentioning
confidence: 86%
“…Numerous deregulated miRNAs are involved in gastric cancer and include miR-146a, miR-155, miR-21, miR-27a, miR-106-93-25, miR-221-222 clusters, and the miR-200 family (23)(24)(25)(43)(44)(45)(46). A growing number of studies also suggest the involvement of miRNAs in various steps of gastric carcinogenesis: from gastritis to metastatic disease (47).…”
Section: Discussionmentioning
confidence: 99%
“…miR-222 has been shown to be up-regulated in gastric cancer, thyroid tumors, pancreatic cancer, childhood B-cell precursor acute lymphoblastic leukemia and hepatic cell cancers (23,(31)(32)(33)(34). The overexpression of miR-222 is found to be correlated with the resistance to hormone treatment and aggressiveness in prostate carcinoma (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PLCD1 and RNF139, two predicted candidate target genes of miR-191, are tumor suppressors in esophageal squamous cell carcinoma and human hereditary kidney cancer, respectively (21,22). miR-93 is up-regulated in gastric cancer tissues compared to the corresponding normal tissues (23). It is also significantly overexpressed in the serum of ovarian cancer patients compared to controls (24).…”
Section: Discussionmentioning
confidence: 99%